Foundations of software science and computation structures : 20th International Conference, FOSSACS 2017, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2017, Uppsala, Sweden, April 22-29, 2017, Proceedings /: 20th International Conference, FOSSACS 2017, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2017, Uppsala, Sweden, April 22-29, 2017, Proceedings. (2017) - Unknown
No abstract available